STRATEGI PEMASARAN PADA KLASTER UBI KAYU (Manihot esculenta) UNTUK MENINGKATKAN DAYA SAING DI KABUPATEN WONOGIRI - Wardani, Irma; Dewi, Tria Rosana; Solikah, Umi Nur; Suwardi; Surya, Ibnu (Journal of Agribusiness, Social and Economic, 2025)
Cluster development to improve performance based on regional commodity specialties by providing recommendations to stakeholders. The cassava cluster is one of the clusters in Wonogiri Regency. This study aims to analyze alternative strategies to be applied to the cassava cluster. The analysis methods used are Internal Factors Evaluation (IFE), External Factors Evaluation (EFE), SWOT analysis, and QSPM. The results of the study show that the IFE analysis is 2.980, while the EFE analysis is 2.512. The cassava cluster is in an aggressive position. The managerial implications of the alternative strategies are market expansion, business development, and productivity improvement. The QSPM results show that the total Attractive Strategy for the market expansion strategy is 4.760, the business development strategy is 5.773, and the productivity improvement strategy is 4.585. In the QSPM matrix, the selected strategy is the one with the highest score, so the chosen strategy is the cluster development strategy. The strategy can be implemented by business actors participating in training related to the cultivation of high-quality cassava and post-harvest processing of cassava. Cassava diversification can be done by processing cassava into mocaf flour or packaging it semi-cooked as frozen cassava. Keywords: Marketing, Cluster, Cassava, SWOT